Interleukin-15 (IL-15) and Anti-C1q Antibodies as Serum Biomarkers for Ectopic Pregnancy and Missed Abortion - Alexandros Daponte; Efthimios Deligeoroglou; Spyros Pournaras; Christos Hadjichristodoulou; Antonios Garas; Foteini Anastasiadou; Ioannis E. Messinis (Clinical and Developmental Immunology)
Given the present lack of clinically useful tests for the accurate diagnosis of ectopic pregnancy (EP), there is a need to select out those immunological factors measured in the maternal serum, as potential biomarkers. Our assumption was that C1q/anti-C1q antibody complexes and serum levels of interleukin-15 (IL-15) may play a role in differentiating abortions (MAs) and EPs and normal pregnancies. We assessed whether their measurement could set the diagnosis in a case control study at 6–8 weeks consisting of 60 women with failed early pregnancy (30 EPs, 30 MAs) and 33 women with intrauterine pregnancies. Normal pregnancies contain anti-C1q antibodies more frequently compared to women with failed pregnancies, the lowest levels being found in EPs, but this lacked statistical significance and anti-C1q could not serve as a marker. However EP pregnancies had elevated IL-15 levels that could statistically significantly differentiate them from MAs and IUPs. Furthermore, when assessing IL-15 for the clinically important differentiation between IUP and EP, we found at a cut-off of 16 pg/mL a negative predictive value of 99 with a sensitivity for diagnosing an EP of 92%. According to these results, serum IL-15 is a promising marker differentiating an MA from an EP.